2023
DOI: 10.1101/2023.03.03.530773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An IL-1β driven neutrophil-stromal cell axis fosters a BAFF-rich microenvironment in multiple myeloma

Abstract: SummaryThe bone marrow is permanently harbors high numbers of neutrophils, and a tumor-supportive bias of these cells could significantly impact bone marrow-confined malignancies. In multiple myeloma, the bone marrow is characterized by inflammatory stromal cells with the potential to influence neutrophils. We investigated myeloma-associated alterations in marrow neutrophils and the impact of stromal inflammation on neutrophil function. Mature neutrophils in myeloma marrow are activated and tumor-supportive, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Considering the connection of iMSCs with MRD, it is worth reevaluating the role of BM stroma-induced drug resistance in MM cells by considering the contribution from the inflammatory state in the MSCs. Equally important is to examine their roles in modulating the immune microenvironment, as recently demonstrated in the iMSC-specific activation of neutrophils [62]. Establishing an in vitro model for iMSCs through cytokine stimulations such as IL-1β represents an important step to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the connection of iMSCs with MRD, it is worth reevaluating the role of BM stroma-induced drug resistance in MM cells by considering the contribution from the inflammatory state in the MSCs. Equally important is to examine their roles in modulating the immune microenvironment, as recently demonstrated in the iMSC-specific activation of neutrophils [62]. Establishing an in vitro model for iMSCs through cytokine stimulations such as IL-1β represents an important step to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…While most of the studies have focused on the immune component 47 , mounting evidence suggests that endothelial cells (EC) and mesenchymal stem cells (MSC) also contribute to the survival and growth of myeloma PC through the production of cytokines and the release of extracellular vesicles 8,9 . Moreover, an enhanced inflammatory signature has been identified in MSC of patients with MM 1012 . However, the role of the non-hematopoietic BM microenvironment in the transition from MGUS to MM remains less understood.…”
Section: Introductionmentioning
confidence: 99%
“…While most of the studies have focused on the immune component [4][5][6][7] , mounting evidence suggests that endothelial cells (EC) and mesenchymal stem cells (MSC) also contribute to the survival and growth of myeloma PC through the production of cytokines and the release of extracellular vesicles 8,9 . Moreover, an enhanced inflammatory signature has been identified in MSC of patients with MM [10][11][12] . However, the role of the non-hematopoietic BM microenvironment in the transition from MGUS to MM remains less understood.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is characterized by significant genetic and genomic heterogeneity between patients and within individual patients 2,3 . Several studies have demonstrated the role of the BM microenvironment in the development and progression of MM and treatment resistance [4][5][6][7][8] . Various mechanisms have been implicated in the expansion and growth of malignant PC.…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms have been implicated in the expansion and growth of malignant PC. For example, the release of matrix metalloproteinases (MMPs) facilitates invasion into nearby tissues and metastasis, or the secretion of interleukins promotes myeloma cell growth or inhibits immune function 7,9 . Moreover, the induction of neutrophil extracellular traps (NETs) formation by neutrophils, or the impairment of T cell function, allows tumor expansion 8,10 .…”
Section: Introductionmentioning
confidence: 99%